2015
DOI: 10.3171/2014.12.spine141062
|View full text |Cite
|
Sign up to set email alerts
|

Spinal intraosseous epidural arteriovenous fistula with perimedullary drainage obliterated with Onyx embolization: case report

Abstract: The authors report an extremely rare case of spinal intraosseous epidural arteriovenous fistula (AVF) with perimedullary vein reflux causing symptoms of myelopathy. The intraosseous fistula tracts were completely obliterated with Onyx embolic agent, resulting in a total resolution of symptoms. The unique features of this case include the rare location of the fistula in the vertebral body and the association of the fistula with a compressive fracture. Imaging studies confirmed these hemodynamic findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 14 publications
(8 reference statements)
1
15
0
Order By: Relevance
“…8 In our cases, 3 underwent TVE, 1 underwent an operation, and the other one was under observation because the symptoms were tolerable. Although trauma was suggested as a cause of SEDAVFs, especially in the osseous type, 19,20 only 1 patient in our study (case 1) was confirmed to have a history of trauma in which a T12 compression fracture was caused by a fall 3 years before the initial presentation. Because the patient's symptoms developed after the trauma and the fistula occurred at the same level, we assumed that the SEDAVF could have been the result of the trauma, despite the long interval.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…8 In our cases, 3 underwent TVE, 1 underwent an operation, and the other one was under observation because the symptoms were tolerable. Although trauma was suggested as a cause of SEDAVFs, especially in the osseous type, 19,20 only 1 patient in our study (case 1) was confirmed to have a history of trauma in which a T12 compression fracture was caused by a fall 3 years before the initial presentation. Because the patient's symptoms developed after the trauma and the fistula occurred at the same level, we assumed that the SEDAVF could have been the result of the trauma, despite the long interval.…”
Section: Discussionmentioning
confidence: 58%
“…16 This study included 5 cases (38.4%) of osseous SEDAVFs, even though only a few cases of SEDAVFs with bone involvement have been reported previously. [18][19][20] The mechanisms of formation of the bone lesion and its clinical significance are uncertain. When planning a treatment option, identification of the osseous type can be important.…”
Section: Discussionmentioning
confidence: 99%
“…[4,9,11,12] ree cases of intraosseous SEAVFs associated with a vertebral compression fracture have been reported in the literature. [2,3,8] Although the precise mechanisms responsible for the development and growth of SEAVFs remain unclear, previous reports speculated about a relationship between these entities and prior surgery or trauma. [2,3,6,8] Here, we describe an extremely rare case of intraosseous thoracolumbar SEAVF involving a previous 12 and L1 vertebral compression fracture, with perimedullary reflux causing symptoms of myelopathy.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3,8] Although the precise mechanisms responsible for the development and growth of SEAVFs remain unclear, previous reports speculated about a relationship between these entities and prior surgery or trauma. [2,3,6,8] Here, we describe an extremely rare case of intraosseous thoracolumbar SEAVF involving a previous 12 and L1 vertebral compression fracture, with perimedullary reflux causing symptoms of myelopathy. Written informed consent was obtained from the patient before the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal epidural arteriovenous fistulas (SEDAVFs) are extremely rare and the pathological process still remains unclear [1][2][3] . Only few cases or case series have been reported in literature 1,2,[4][5][6][7][8][9][10][11][12] .It is postulated that, in SEDAVF, branches of the radicular artery directly communicate with the epidural venous plexus and often manifests clinically as radiculopathy 1 .…”
Section: Introductionmentioning
confidence: 99%